Implication of palynological techniques for the authentication of adulterated drugs traded with the same name in different herbal markets of district Lahore, Pakistan. Issue 6 (25th February 2019) - Ramzan, Sehrish; Shaheen, Shabnum; Hussain, Khadim; Sharifi‐Rad, Javad; Khan, Muhammad Asaf; Harun, Nidaa; Jaffer, Mehwish; Khan, Farah
Abstract: Adulteration in traded medicinal plants is a significant issue nowadays and use of these adulterated medicinal plants can impose harmful impact to end user. However, this problem can be overcome by ensuring the identification of traded medicinal plants which are used in making different herbal medicines. In this regard, palynological markers are considered to be an important taxonomic tool in the identification of original medicinal plant from its adulterant. Hence this study attempted to provide particular reliable palynological markers for distinguishing selected medicinal plants from their adulterants, that is, Cinnamomum verum versus Canella winterana, Cinnamomum tamala versus Cinnamomum obtusifolium, Gymnema sylvestre versus Gymnema lactiferum, Artemisia maritima versus Artemisia absinthium, Achillea millefolium versus Adhatoda vasaka, Sphaeranthus indicus versus Sphaeranthus africanus, Averrhoa carambola versus Butea monosperma, and Morus nigra versus Morus alba . Results demonstrated great variations in multiple palynological characters between original medicinal plant and its adulterant such as in pollen size, shape, colpi length, exine, intine thickness, and fertility. In equatorial view, circular to spheroidal shape of pollen was found in A. millefolium while oblate shape was observed in A. vasaka . Similarly B. monosperma pollen was 34 μm, whereas pollen of its adulterant A. carambola was 21 μm. Moreover, colpi length of A. maritima was 11.8 μm, whereas 4.5 μm in A. absinthium . Hence it can be concluded that palynological characters are commendably helpful in identification of genuine medicinal plant from its adulterant. Abstract : Adulterated drugs identification. Implication of palynological techniques for the authentication of adulterated drugs traded with the same name in different herbal markets of district Lahore, Pakistan was done for the first time on the basis of LM and SEM and the research was found very significant for taxonomic investigations of the adulterated plants.